2002
DOI: 10.1038/sj.onc.1205347
|View full text |Cite
|
Sign up to set email alerts
|

Anti-neovascular therapy using novel peptides homing to angiogenic vessels

Abstract: Cancer chemotherapy targeted to angiogenic vessels is expected to cause indirect tumor regression through the damage of the neovasculature without the induction of drug resistance. To develop a tool for neovasculaturespeci®c drug delivery, we isolated novel peptides homing to angiogenic vessels formed by a dorsal air sac method from a phage-displayed peptide library. Three distinct phage clones that markedly accumulated in murine tumor xenografts presented PRPGAPLAGSWPGTS-, DRWRPALPVVLFPLH-or ASSSYPLIHWRPWARpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(80 citation statements)
references
References 29 publications
2
78
0
Order By: Relevance
“…After determination of the epitope sequences of the obtained phages and modi¢cation of liposomes with these peptides, the APRPG-modi¢ed liposome was revealed to be favorable for the active targeting of the angiogenic endothelium. Furthermore, anti-neovascular therapy using this type of liposome as a carrier of adriamycin markedly suppressed tumor growth possibly through a cytotoxic e¡ect of the drug against angiogenic endothelial cells [10], although an increase in the local concentration of adriamycin released from the liposomes may have partly contributed to this enhanced e⁄cacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After determination of the epitope sequences of the obtained phages and modi¢cation of liposomes with these peptides, the APRPG-modi¢ed liposome was revealed to be favorable for the active targeting of the angiogenic endothelium. Furthermore, anti-neovascular therapy using this type of liposome as a carrier of adriamycin markedly suppressed tumor growth possibly through a cytotoxic e¡ect of the drug against angiogenic endothelial cells [10], although an increase in the local concentration of adriamycin released from the liposomes may have partly contributed to this enhanced e⁄cacy.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, we recently isolated peptides speci¢c for tumor angiogenic vasculature by using a phage-displayed peptide library [10,11]. In vivo biopanning of phage-displayed peptide library in angiogenic model mice prepared by the dorsal air sac method [12] enabled us to isolate speci¢c phage clones having the ability to bind only to angiogenic vessels, not to tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…6) Tumor Implantation and Therapeutic Experiment The therapeutic experiment was performed according to the procedure described previously. 7) Meth A sarcoma cells were grown in BALB/c male mice (Japan SLC Inc. Shizuoka, Japan) under an appropriate schedule, and were diluted with saline to obtain a 5ϫ10 6 cells/ml suspension. Then 0.2 ml of the suspension was injected subcutaneously into the posterior flank of 5-week-old BALB/c male mice.…”
Section: Methodsmentioning
confidence: 99%
“…10) In the present study, we identified a novel peptide, LFPLH, derived from DRWRPALPVVLFPLH which was originally isolated from among homing peptides to angiogenic sites using a phagedisplayed random peptide library. 6) Phage-displayed random peptide libraries are useful to obtain specific peptides interacting with target molecules such as receptors and adhesion molecules. 11,12) The present data indicate that LFPLH may inhibit angiogenesis in a manner similar to WRP-containing peptides, the antiangiogenic activity of which was clarified in our previous study.…”
Section: Fig 3 Effect Of Lfplh and Its Shuffled Peptide On Huvec MImentioning
confidence: 99%
“…13 In addition, some peptides selected with phage display have also been used as antagonists of VEGF to its receptor. [14][15][16] In addition, a cyclic peptide corresponding to amino acids 79-93 of the VEGF sequence was reported to inhibit angiogenesis. 17 Its biological properties make VEGF an important therapeutic target, and it has been shown that the anti-VEGF signal pathway can inhibit tumor growth in vivo.…”
Section: A Fusion Protein With the Receptor-binding Domain Of Vasculamentioning
confidence: 99%